FTIR spectroscopy for COVID-19 detection in saliva - Bunaciu, Andrei A. (Henry Stewart Talks, 2023)
FTIR spectroscopy for COVID-19 detection in saliva, COVID-19 diagnosis methods, Infrared spectroscopy, Infrared based saliva screening test for COVID-19, Fourier-Transform Infrared (FTIR)